The Creativity Of Ibn Abi Al-Dunya (d. 281/894) In Purifying The Human Soul : An Analytical Study - Iman Najim Abd Al-Rahman Khalaf
This thesis sheds light on the outcome that results from the integration of creativity and holding onto ultimate goals. Ibn Abi Al-Dunya, a well-known educator and scholar, has proven to possess creative skills among his other characteristics. He was a man of belief who strived his best to leave a positive imprint behind. His life during the ‘golden age’ of the Islamic civilization and his witness to the new luxurious life that accompanied it, placed burdens over him that led to the route of reform. During his lifetime, he managed to write numerous books in various fields, focusing on topics related to asceticism. This thesis studies forty-nine books of Ibn Abi Al-Dunya’s works that are related to the purification of the human soul at the level of individuals and the level of the society. It attempts to examine Ibn Abī Al-Dunyā’s creativity and methodology in purifying the human soul at the individual and societal levels. It also aims at exploring the life and personality of Ibn Abi Al-Dunya and analyzing his works. The thesis examines the concept of purification of the soul from the Islamic perspective and analyzes the contributions of Ibn Abi Al-Dunya on purifying the human soul at both the individual and societal levels. It evaluates the creative traits and methodology in purifying the soul. This thesis employs a historical and analytical approach toward data gathering and content analysis to help identify the main features and elements of purification of the human soul from the Qur’an and the Sunnah. It is a library-based study that depends mainly on theoretical dad provided by written sources. The study found that Ibn Abi Al-Dunya followed a comprehensive methodology based on the Islamic doctrine and his extensive educational experience with thorough contact with different classes of his society. His method successfully introduced the topic of purification from all its angles in a creative way. It also established the concept of purification and set the appropriate techniques to achieve it. The analysis shows that his method is based on three main principles: belief (al-ʿaqidah), morals (al-akhlaq), worship and social dealings (al-ʿibadah wa al-muʿamalat).